TEC2Ne: a physics-informed deep learning framework for reconstructing ionospheric electron density profiles from global TEC maps - Chenghao Li; Hanxian Fang; Chao Xiao; Die Duan; Yang Lin; Hongtao Huang; Ganming Ren; Han Wu; Chuyue Zhou; Haiyang Zheng; Xuhui Shen; Xiaoqun Cao (GPS Solutions, 2026)

Endogenous rGRF4-GIF1 enables high-efficiency transformation and systemic trichome induction without pleiotropic defects in strawberry - Maoqing Ye; Xuhui Wang; Liyuan Yang; Xinlan Wang; Jiayi Chen; Kai Huang; Heqing Liu; Lixuan Lin; Zhenbiao Yang; Chizuko Yamamuro; Ying Liu (Plant Science, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

The influence of perforation stimulation for natural gas hydrates reservoir on seafloor stability - Lin Yang; Qianyong Liang; Xuhui Zhang; Yudong Huang; Xuemin Wu; Xiaofeng Dou; Zhigang Wang (Ocean Engineering, 2026)

Resveratrol synergizes with chloroquine to inhibit the malignant progression of oral squamous cell carcinoma by regulating KIF11 - Jianfeng Dong; Qing Zhu; Xuhui Fan; Shuning Li; Lin Lu; Guojie Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Physics-informed deep learning for hillslope subsurface flow prediction: integrating soil moisture deficit constraints - Xiaole Han; Man Gao; Jintao Liu; Hai Yang; Haoming Lin; Xuhui Shen (Journal of Hydrology, 2026)

Joint effects of manure application and tetracycline contamination on plant growth and tetracycline-resistance gene diffusion in a soil-pakchoi system - Xuhui LI; Wenxi JIANG; Deyuan ZHU; Lin LI; Jimei HE; Huan LIU; Wencong MA; Ruichao GUO; Yulong WANG (Pedosphere, 2026)

Dynamic variations of near-surface temperature and moisture at a desertified permafrost site on the Qinghai-Tibet Plateau - Zhanju Lin; Nuocheng Li; Xuhui Wang; Xingwen Fan; Wenjiao Li; Xuyang Wu; Peng Zhang (Cold Regions Science and Technology, 2026)

Assessing the impacts of climate warming and engineering activities on the thermal regime of permafrost in the Kunlun Mountains, Qinghai-Tibet Railway - Zhanju Lin; Xuhui Wang; Xuyang Wu; Wenjiao Li; Peng Zhang; Nuocheng Li; Xingwen Fan (Cold Regions Science and Technology, 2026)

Mechanistic impacts of extra-long tunnel construction on eco-environmentally vulnerable zones: Coupled system dynamics and LSTM-Transformer modelling - Yan Yin; Weixing Bao; Hanqing Lu; Zhiming Huang; Xuhui Lin (Tunnelling and Underground Space Technology, 2026)

Concise seismic fragility computation method using ground motion input clustering under soil-structure interaction - Xuhui Liu; Jianbo Li; Zhiyuan Li; Gao Lin (Soil Dynamics and Earthquake Engineering, 2026)

Distribution characteristics of secondary embankment diseases in permafrost regions of Qinghai Province and their relationship with local factors - Peng Zhang; Lei Liu; Yangyang Xie; Xuyang Wu; Xingwen Fan; Wenjiao Li; Nuocheng Li; Xuhui Wang; Fujun Niu; Zhanju Lin (Cold Regions Science and Technology, 2026)

Study on the ground-air temperature relationship under microenvironmental differences in the warm permafrost region of the Tibetan Plateau - Nuocheng Li; Zhanju Lin; Xingwen Fan; Yanhe Wang; Wenjiao Li; Qiang Gu; Wenlong Pang; Xuhui Wang; Peng Zhang (Cold Regions Science and Technology, 2026)

Esculin Alleviated NLRP3 Inflammasome Activation by Inducing PINK1/Parkin-Mediated Mitophagy in Cerebral Ischemia–Reperfusion Injury - Jinyu Lin; Bowen You; Xin Yang; Xue Li; Wenjuan Sun; Zhongyu Xu; Yi Zhang; Xuhui Tong; Shuying Dong (Molecular Neurobiology, 2026)

Projecting city-scale energy performance under future weather scenarios through urban building energy modelling incorporating cluster archetypes - Jingfeng Zhou; Jiying Chen; Kaixuan Wang; Bingyu Xu; Xuhui Lin; Jiayi Yan; Meng Wang (Sustainable Cities and Society, 2025)

Ground subsidence monitoring and prediction based on InSAR and CNN-BiGRU-Attention: A case study of Chengdu - Zhihua Zhang; Qiang Lin; Haowen Yan; Xinyu Zhu; Xinxiu Zhang; Shuwen Yang; Chunlin Huang; Yueling Shi; Jie Hu; Xuhui Li; Li Hou; Lujia Zhao; et al. (Engineering Geology, 2025)

An inversion method for air to land surface temperature considering different slope orientations in a high-altitude permafrost region - Wenjiao Li; Zhanju Lin; Xingwen Fan; Lei Liu; Xuyang Wu; Nuocheng Li; Peng Zhang; Xuhui Wang (Atmospheric Research, 2025)

PSeqNet: A crop phenology monitoring model accounting for phenological associations - Qiyu Tian; Hao Jiang; Renhai Zhong; Xingguo Xiong; Xuhui Wang; Jingfeng Huang; Zhenhong Du; Tao Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Characterisation of greenhouse gas emissions from temporary wastewater treatment plants under different operation modes - Yan Yin; Weixing Bao; Bowen Che; Hanqing Lu; Xuhui Lin (Process Safety and Environmental Protection, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Neurotoxicity and aggressive behavior induced by anesthetic etomidate exposure in zebrafish: Insights from multi-omics and machine learning - Xuewei Li; Xuhui Lin; Zheng Zhang; Zile Zhuang; Yihan Li; Yuxuan Luo; Yupeng Pan; Qizhi Luo; Xuncai Chen (Aquatic Toxicology, 2025)

From points to patterns: An explorative POI network study on urban functional distribution - Xuhui Lin; Tao Yang; Stephen Law (Computers, Environment and Urban Systems, 2025)

Long-term efficient electrosynthesis of adipic acid and hydrogen by heterostructural molybdenum-nickel alloy electrode - Cong Lin; Haoyun Lu; Xuhui Ren; Bin He; Xu Peng; Pengzuo Chen (Chemical Engineering Journal, 2025)

Lithological impact on topsoil organic carbon storage of karst forest soils shaped by aggregate pool complexity and their molecular composition - Qingmei Lin; Shuotong Chen; Xiao Feng; Thammavongsa Sounilan; Kun Cheng; Xuhui Zhang; Rongjun Bian; Xiaoyu Liu; Yan Wang; Marios Drosos; Jufeng Zheng; Lianqing Li; et al. (Applied Soil Ecology, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Effects of thermal oxidation interaction via various polar lipid and myofibrillar proteins on the aroma formation in large yellow croaker - Tingting Zhang; Ke Zhang; Xinyi Qi; Sijia Lin; Lei Qin; Xuhui Huang (Food Bioscience, 2024)

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

Deep-sea microplastics aging and migration exerted by seamount topography and biotopes in the subtropic Northwest Pacific Ocean - Huige Guo; Xiaochen Wang; Hong Cheng; Zhaohe Luo; Jieliang Huang; Hongzhe Chen; Jinling Pang; Kunning Lin; Shuyuan Huang; Xuhui Zhang; Yuanbiao Zhang (Science of The Total Environment, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Pb isotopic fingerprinting of uranium pollution: New insight on uranium transport in stream-river sediments - Jin Wang; Haiyao Hu; Ke Lin; Xudong Wei; Jingzi Beiyuan; Xinni Xiong; Yuebing Wan; Pengyuan Deng; Hanyu Wu; Mingliang Kang; Juan Liu; Xuhui Dong (Journal of Hazardous Materials, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Long-term species-level observations indicate the critical role of soil moisture in regulating China's grassland productivity relative to phenological and climatic factors - Shuai An; Xiaoqiu Chen; Fangjun Li; Xuhui Wang; Miaogen Shen; Xiangzhong Luo; Shilong Ren; Hongfang Zhao; Yan Li; Lin Xu (Science of The Total Environment, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

Life cycle assessment of an efficient biomass power plant supported by semi-closed supercritical CO2 cycle and chemical looping air separation - Yuan Wang; Lin Zhu; Yangdong He; Xingyan Zeng; Qiang Hao; Yue Huang; Xuhui Han (Science of The Total Environment, 2024)

Comparison of arsenate and arsenite removal behaviours and mechanisms from water by FeLa binary composite (hydr)oxides - Yulong Wang; Chen Guo; Lin Zhang; Yanhong Liu; Yangyang Wang; Xuhui Li (Journal of Water Process Engineering, 2024)

A novel cost-effective flow-through electrode based on polyacrylonitrile carbon fiber for enhancing micropollutant degradation via electro-Fenton - Yu Huang; Lin Shi; Xiaofei Chen; Liandong Zhu; Xuhui Mao; Tao Xu; Hua Zhu; Xu Wang (Chemical Engineering Journal, 2023)

Influence of copper and aging on freely dissolved tetracycline concentration in soil - Ruichao Guo; Deyuan Zhu; Jimei He; Wencong Ma; Lin Li; Xuhui Li; Yulong Wang (Environmental Science and Pollution Research, 2023)

Dynamic pore modulation of contracted carbon fiber filter for wastewater treatment: Filtration performance and in-situ regeneration mechanism - Tao Xu; Lin Shi; Senlin Shao; Hui Wang; Yu Huang; Lei Xing; Re Xia; Ruggero Rossi; Liandong Zhu; Hua Zhu; Wulin Yang; Xuhui Mao; et al. (Chemical Engineering Journal, 2023)

Does urban scale borrowing aggravate carbon and air pollution emissions? - Zhongyao Cai; Xuhui Ding; Huaxing Lin; Ziqian Zhou; Xinyu Yang; Ping Jiang (Environmental Impact Assessment Review, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Nonhydrostatic simulation of internal lee wave-induced turbulence mixing: A comparative study of second-moment closure mixing schemes for an idealized marginal sea sill topography - Shifan Wang; Lianxin Zhang; Xuefeng Zhang; Lei Lin; Xuhui Hu (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Investigation of the Spatial Correlation of Rock Crack Propagation Based on Graph Theory - Chunlai Wang; Biao Wang; Changfeng Li; Lin Huang; Liang Sun; Xuhui Xue; Peng Cao (Rock Mechanics and Rock Engineering, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Divergent seasonal responses of carbon fluxes to extreme droughts over China - Ying Deng; Xuhui Wang; Tongping Lu; Haochun Du; Philippe Ciais; Xin Lin (Agricultural and Forest Meteorology, 2023)

Statistical study on the CSES radio occultation data and its quality control in electron density inversion - Shengfeng Gu; Chengkun Gan; Yun Qing; Jian Lin; Xiaomin Luo; Xuhui Shen; Jingnan Liu (GPS Solutions, 2022)

Warming effects on grassland productivity depend on plant diversity - Junjiong Shao; Xuhui Zhou; Kees Jan van Groenigen; Guiyao Zhou; Huimin Zhou; Lingyan Zhou; Meng Lu; Jianyang Xia; Lin Jiang; Bruce A. Hungate; Yiqi Luo; Fangliang He; et al. (Global Ecology and Biogeography, 2022)
Aim Climate warming and biodiversity loss both alter plant productivity, yet we lack an understanding of how biodiversity regulates the responses of ecosystems to warming. In this study, we examine how plant diversity regulates the responses of grassland productivity to experimental warming using meta‐analytic techniques. Location Global. Major taxa studied Grassland ecosystems. Methods Our meta‐analysis is based on warming responses of 40 different plant communities obtained from 20 independent studies on grasslands across five continents. Results Our results show that plant diversity and its responses to warming were the most important factors regulating the warming effects on plant productivity, among all the factors considered (plant diversity, climate and experimental settings). Specifically, warming increased plant productivity when plant diversity (indicated by effective number of species) in grasslands was lower than 10, whereas warming decreased plant productivity when plant diversity was greater than 10. Moreover, the structural equation modelling showed that the magnitude of warming enhanced plant productivity by increasing the performance of dominant plant species in grasslands of diversity lower than 10. The negative effects of warming on productivity in grasslands with plant diversity greater than 10 were partly explained by diversity‐induced decline in plant dominance. Main conclusions Our findings suggest that the positive or negative effect of warming on grassland productivity depends on how biodiverse a grassland is. This may mainly be due to differences in how warming may affect plant dominance and subsequent shifts in interspecific interactions in grasslands of different plant diversity levels.

Development and validation of gene-specific KASP markers for YrAS2388R conferring stripe rust resistance in wheat - Yanling Hu; Xuhui Huang; Fang Wang; Yu He; Lihua Feng; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; Jiajie Wu; Lianquan Zhang; Bihua Wu; et al. (Euphytica, 2021)

Hippocampal atrophy and functional connectivity disruption in cirrhotic patients with minimal hepatic encephalopathy - Weiwen Lin; Xuhui Chen; Yong-Qing Gao; Zhe-Ting Yang; Weizhu Yang; Hua-Jun Chen (Metabolic Brain Disease, 2019)

Lhx9 Is Required for the Development of Retinal Nitric Oxide-Synthesizing Amacrine Cell Subtype - Revathi Balasubramanian; Andrew Bui; Xuhui Dong; Lin Gan (Molecular Neurobiology, 2018)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

Effects of rainfall amount and frequency on vegetation growth in a Tibetan alpine meadow - Baocheng Zhang; Junji Cao; Yanfen Bai; Xuhui Zhou; Zhigang Ning; Songjie Yang; Lin Hu (Climatic Change, 2013)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)